A Community‐Based Intervention Program's Effects on Dietary Intake Behaviors - Chang, Mei‐Wei; Brown, Roger; Nitzke, Susan (Obesity (Silver Spring, Md.), 2017)
Objective To evaluate the effect of a community‐based lifestyle behavioral intervention on intakes of fat, fruits, vegetables, fast foods, and beverages in low‐income young mothers with overweight or obesity. Methods Participants were randomly assigned to an intervention (watching video lessons at home plus peer support group teleconferences) or a comparison group. General linear mixed model analyses were utilized to determine mean differences between the groups (212 intervention, 126 comparison) immediately following and 3 months (196 intervention, 115 comparison) after the intervention. Results Immediately after the intervention, the intervention group had significantly lower mean scores in intakes of fat (effect size [d] = 0.24), fast foods (d = 0.33), and non–sugar‐sweetened beverages (d = 0.27) than the comparison group. No significant group differences were observed for intakes of fruits, vegetables, or sugar‐sweetened beverages. Three months after the intervention, no significant group differences were observed for intakes of fat, fruits, vegetables, fast foods, and both sugar‐ and non–sugar‐sweetened beverages. Conclusions The intervention group improved dietary intakes of fat and fast foods but not fruits, vegetables, or beverages over the short term. Our intervention had no long‐term effect on dietary intake behaviors.